Quasi-Objects of Art-Architecture in Exhibit: Revisiting Mulino Stucky Project As a Transversal Exhibition in The Venice Biennale of 1975 - Bilge Beril Kapusuz Balcı (Livenarch+ Journal)
In the late 1960s and 70s, architects and artists blurred disciplinary boundaries, with architects exploring installation as a form of spatial production and artists using architectonic forms. This practice, described as “making (for) the exhibition,” flattens disciplinary hierarchies and highlights the repetition of spatial works in large-scale art and architecture exhibitions. The “art-architecture coupling” moves beyond visual arts and architecture, necessitating a redefinition of categories and practitioners. Drawing on philosophers Peter Osborne and Eric Alliez’s concepts of “transdisciplinary” and “transcategorial” practices, this paper examines how exhibitions function as processual and performative “projects” that suspend the work/viewer division, granting equal “agency” to objects and subjects. Using Michel Serres and Bruno Latour’s idea of the “quasi-object,” the paper questions how these quasi-objects operate within exhibitions to transform or reassemble dynamic social spaces. The Venice Biennale, specifically its 1975 Mulino Stucky exhibition, is revisited as a pivotal moment when the Biennale shifted from academic art toward a socially-oriented articulation of visual arts and architecture. Through archival visual documents, the Mulino Stucky exhibition is reassessed to reveal the material and social relations of its performative processes, highlighting the role of quasi-objects in shaping the exhibition space.